Sevoflurane for Analgesia—Testing a Modified Vaporiser for Delivery. Issue 4 (July 2015) - Miller, L. A.; Makins, H.; Eltringham, R.; Neighbour, R.
The Diamedica Sevoflurane Inhaler (Diamedica UK Ltd, Bratton Fleming, UK) (DSI) is a breathing system which includes a modification of an existing vaporiser (Diamedica Draw-over Vaporiser, Diamedica UK Ltd, Bratton Fleming, UK), to enable the delivery of 0.8% sevoflurane. Previous studies have suggested that self-administered sevoflurane at sub-anaesthetic concentration can provide useful pain relief during the first stage of labour and that it may be more effective than Entonox. Further research and potential clinical use have been impeded by the lack of a practical delivery system. In this study, the performance of two versions of the DSI (DSI-1 and DSI-2) was investigated. DSI-1 was tested over a range of minute volumes (1 to 30 l/min) and ambient temperatures (10°C to 40°C). The sevoflurane output increased unacceptably with rising ambient temperature, therefore the design was modified to create the DSI–2. The results from testing this revised version are also described. Mean sevoflurane output from the DSI-2 was found to be within a clinically acceptable range at the minute volumes tested (0.78% to 0.88%) and ambient temperatures tested (0.69% to 0.9%). Based upon these results, the authors propose to undertake further studies of sevoflurane analgesia using the DSI-2.